Hugo Orlando Quevedo, Pelagio B. Luna. Olvidado apóstol del credo radical, Buenos Aires, Lerner Editorial, 2003, 220 pp. - Rosa, María Fernanda de la (2004)
Fil: Rosa, María Fernanda de la. Investigador independiente; Argentina